A Critique of the Unanticipated Powers Of The State Security Service In Nigeria and the Validity of their Source - Etudaiye, Mohammed Enesi; Etudaiye, Muhtar Adeiza (NIU Journal of Social Sciences, 2017)
Recently, one of Nigeriaâ€™s intelligence and security agencies, the State Security Service (SSS) embarked on the search of the residences of and arrest of politicians and judges on allegations of official corruption. This move was met with both public approval and outcry. The focal point of the diverse contentions became whether the SSS possessed such powers and by what authority. This was a healthy culmination in the sense that it kick-started a debate that has, however, glossed over critical but unforeseen authorities. This article examines and ascertains the â€œshadowyâ€ authorities on the true scope of the powers of the SSS. Keywords: Critique, Powers, State, Security, Nigeria, Validity, Source